An alignment effect of concentrated and family ownership on carbon emission performance: The case of Indonesia - Achsanul Qosasi; Hendra Susanto; Rusmin Rusmin; Emita Astami; Alistair Brown (Cogent Economics & Finance, 2022)
This study considers the effect of ownership characteristics on carbon emission disclosures using balanced panel data and a matched-pair design of 124 annual reports of non-financial firms listed on the Indonesia Stock Exchange (IDX) during 2017-2019. The main result from multivariate analysis reveals that firms with concentrated and family ownership tend to disclose more carbon emission information. This finding suggests that the stewardship qualities of concentrated and family-controlled entities align with carbon emission accountability and strategies to reduce emissions. Our additional analyses show that firms with family board members generate more carbon emission information. Finally, the analysis of nonlinear relationships confirms both monitoring and expropriation effects of family ownership on carbon emission performance. Therefore, the results of this study suggest that considerable work is needed for all non-financial listing firms to specify emission reduction targets and target years, quantify emission reductions and associated costs or savings, and factor costs of future emissions into capital expenditure planning. This study makes a valuable contribution to the family business and carbon emissions, a contribution of considerable interest to a broad interdisciplinary audience, including family business owners, managers, governments, and academics.
Keywords: 330; carbon emission disclosure; family-controlled firm; Indonesia; Ownership characteristics; stewardship theory